DAMPAK LIBERALISASI PERDAGANGAN TERHADAP TINGKAT EMPLOYMENT DAN UPAH PADA INDUSTRIMANUFAKTUR PADAT KARYA DI INDONESIA - Susanto, Joko (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2006)
In line with trade liberalization, all of trade barrier such as tariff and non-tariff barrier would be reduced. Indonesia would go into a free trade era. The objective of research is to investigate short and long run effect of trade liberalization on employment and wages of labor-intensive industries.By regressing based on panel data, the results show that trade liberalization via tariff reducing would raise the employment and wage of labor intensive industries in the short and long run. Tariff reduction increases demand for the economys abundant factor (labor), driving wages higher. In the long run, capital is mobile between sectors, generates the higher of capital. The higher of capital implies of an increasing marginal product of labor, driving wages higher.